Analysis of Lead (Pb) and Cadmium (Cd) in water spinach (Ipomoea aquatica Forks.) in a swamp with domestic wastewater - Suraida, Suraida; Syefrinando, Boby; Alfian, Alfian; Fistoni, Fistoni (Jurnal Biologi Udayana, 2021)
This study aimed to determine the content of lead (Pb) and cadmium (Cd) in water spinach ( Ipomoea aquatica Forks.) growing in swamps where household wastewater flows. This type of study is observational, carried out using a descriptive approach through heavy metal testing in the laboratory. The results showed that the parts of the plant that accumulated the most heavy metals were roots, followed by stems, while leaves did not contain metals.  Root organs contained 0.0146 mg/kg of Pb and 0.0018 mg/kg of Cd metal.  The stem organ section contains 0.0012 mg/kg of lead and 0.000867 mg/kg of Cd. All are still below the maximum limit of metal contamination for foodstuffs, and therefores still safe for public consumption.